2012
DOI: 10.1371/journal.pone.0046305
|View full text |Cite
|
Sign up to set email alerts
|

Outer Segment Formation of Transplanted Photoreceptor Precursor Cells

Abstract: Transplantation of photoreceptor precursor cells (PPCs) into the retina represents a promising treatment for cell replacement in blinding diseases characterized by photoreceptor loss. In preclinical studies, we and others demonstrated that grafted PPCs integrate into the host outer nuclear layer (ONL) and develop into mature photoreceptors. However, a key feature of light detecting photoreceptors, the outer segment (OS) with natively aligned disc membrane staples, has not been studied in detail following trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
60
2
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(69 citation statements)
references
References 30 publications
2
60
2
4
Order By: Relevance
“…Rod a-transducin is one of the last components of the phototransduction pathway to be expressed in development and is later than a number of proteins involved in outer segment formation, such as peripherin-2 [59]. Further studies at the ultrastructural level, similar to those performed by Ader and colleagues at 3 weeks post-transplantation [5], would be required to confirm the time-course of outer segment elaboration. Nonetheless, the onset of visual function, as assessed by optokinetic head tracking, correlates very well with the expression of rod atransducin in the integrated donor cells.…”
Section: Maturation Of Donor Cells and Onset Of Functionmentioning
confidence: 97%
See 1 more Smart Citation
“…Rod a-transducin is one of the last components of the phototransduction pathway to be expressed in development and is later than a number of proteins involved in outer segment formation, such as peripherin-2 [59]. Further studies at the ultrastructural level, similar to those performed by Ader and colleagues at 3 weeks post-transplantation [5], would be required to confirm the time-course of outer segment elaboration. Nonetheless, the onset of visual function, as assessed by optokinetic head tracking, correlates very well with the expression of rod atransducin in the integrated donor cells.…”
Section: Maturation Of Donor Cells and Onset Of Functionmentioning
confidence: 97%
“…By transplanting cells isolated from the developing retina at a stage when rod photoreceptors are immature, we have shown that the non-neurogenic, adult retinal environment is able to incorporate and maintain new photoreceptors for many months [1,2]. These new photoreceptors form synaptic connections with inner retinal neurons, generate outer segments, and are capable of restoring rod-mediated vision in models of retinal degeneration [3][4][5][6]. Importantly, we were able to show that these results are only achieved using postmitotic photoreceptor precursor cells but not progenitor cells or photoreceptors at other stages of development [1,3,7,8], a finding supported by others [9,10].…”
mentioning
confidence: 99%
“…[12][13][14]18,19 We investigated whether newly-specified RGCs could be used intravitreally to treat optic neuropathies, using a rotenone-induced model of LHON. Retinas were dissociated from embryonic day 16 and 17 (E16 and E17) and postnatal Day2 (pn2) eGFP mice; within the timeframe for RGC specification.…”
Section: Stem Cell Transplantationmentioning
confidence: 99%
“…Fetal retinal sheet transplants have resulted in long-term visual improvements in different animal models of retinal degeneration (4,(6)(7)(8) and in patients (9), and have shown to integrate and synaptically connect with a degenerated retina (6,8). (II) The second approach is injection of dissociated photoreceptor precursors (10)(11)(12)(13)(14)(15). Studies have shown that a small percentage of subretinally injected photoreceptor precursor cells can integrate in the photoreceptors layer, form synaptic terminals (10,15) and outer segments (14,15).…”
mentioning
confidence: 99%
“…(II) The second approach is injection of dissociated photoreceptor precursors (10)(11)(12)(13)(14)(15). Studies have shown that a small percentage of subretinally injected photoreceptor precursor cells can integrate in the photoreceptors layer, form synaptic terminals (10,15) and outer segments (14,15). However, this requires the presence of an outer nuclear layer in the host retina; transplanted photoreceptor progenitors do not develop proper morphology in recipients with severe loss of photoreceptors (10,11,16).…”
mentioning
confidence: 99%